Complementarity of Different SDS‐PAGE Gel Staining Methods for the Identification of Short Open Reading Frame‐Encoded Peptides. Issue 19 (19th August 2020) - Kaulich, Philipp T.; Cassidy, Liam; Weidenbach, Katrin; Schmitz, Ruth A.; Tholey, Andreas
Abstract: Short open reading frame‐encoded peptides (SEP) have been identified across all domains of life and are predicted to be involved in many biochemical processes, however, for the vast majority of SEP their biological function is still unknown. Optimized methodologies have to be used for the mass spectrometric analysis of SEP, because traditional methods of bottom‐up proteomics show a bias against small proteins. Here, different staining methods for SDS‐PAGE gels prior in‐gel digestion following LC‐MS/MS analysis for the identification of SEP in the archaeon Methanosarcina mazei are investigated. In total, 45 SEP with at least one high confidence (FDR <1%) unique peptide and five consecutive b‐ or y‐ions in the MS2 spectrum are identified. The staining methods provide complementary data. The highest number of SEP are identified in the samples stained with Coomassie brilliant blue. However, the highest quality of the identified SEP is achieved in the samples without staining. These comprehensive data sets demonstrate that in‐gel digestion is well suited for the identification of SEP.